Identification, Cause and Surgical Management of Traumatic Fibroma in the Jugal Mucosa: A Case Report - , João Paulo Assem Bernardo; , Jefferson Pires da Silva Júnior; , Jorge Henrique de Sousa Martins; , Pedro Paulo Lopes de Almeida; , Ana Paula Ferreira de Souza; , Flávio Lima do Amaral Silva; , Jeconias Câmara; , Leandro Coelho Belém (Archives of Current Research International, 2024)
Aims: the objective of the present study is to report a clinical case aimed at the diagnosis and treatment of a traumatic fibroma located in the region of the unilateral buccal mucosa based on clinical and histopathological examination. Case Report: A 43-year-old male patient, melanoderma, attended the Nilton Lins University dental clinic reporting the existence of a large nodule in the cheek region. Based on the clinical appearance of the lesion, the diagnostic hypothesis of traumatic fibroma was established; therefore, the surgical excision of the lesion was determined for subsequent referral to confirm the hypothesis. The removed content was transferred to a container containing a 10% formaldehyde solution and sent to the Department of Pathology and Legal Medicine of the Federal University of Amazonas for histopathological analysis, which disclosed benign epithelial thickening with parakeratosis and underlying connective tissue hyperplasia. Given the characteristics presented in the analyzed histological picture, the definitive diagnosis was reactive fibroepithelial hyperplasia. Conclusion: Establishing a preliminary diagnosis of the lesion was essential for planning the surgical procedure. The use of the conventional technique for the removal of the reactive fibroepithelial hyperplasia obtained satisfactory results, both for the postoperative recovery and for the infeasibility of recurrence, thus providing satisfactory comfort to the patient.